The Relationship Between Self-Determination and the Mathematics Learning Outcome of Senior Highschool Students at Payakumbuh City - Ahdi, Redha Andika; Duryati (Causalita, 2024)
This study aims to determine the relationship between self-determination and mathematics learning achievement in high school students in Payakumbuh City. This research uses quantitative methods with correlational quantitative research design. The population in this study were active high school students in Payakumbuh with a total of 73 subjects. Data collection using a scaled questionnaire about self-determination and mathematics learning achievement as seen from the results of semester report cards in mathematics which are prepared based on existing theories. The data were processed using descriptive statistical tectics (mean and SD) and were intended to describe the relationship between two variables. The results showed that there was a significant positive relationship between self-determination and mathematics learning achievement. r = 0.325; p = 0.005 (p> 0.05) which means that if the higher self-determination, the higher the mathematics learning achievement and conversely, if the lower self-determination, the lower the mathematics learning achievement. The results of this research can be used by schools to understand self-determination and can be used as a reference for developing mathematics learning programs so that students can understand self-determination and have the awareness to increase self-determination to achieve better mathematics learning achievement.